Pengaruh Citra Merek, Kualitas Produk dan Kepercayaan terhadap Keputusan Pembelian pada E-Commerce Shopee Mall di Kota Batam - Ginting, Zilhi Ziyati Br; Evyanto, Winda (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Online purchasing decisions in e-commerce are increasingly influenced by intangible factors such as consumer perceptions of brand credibility, product reliability, and platform trustworthiness. This study addresses a key issue faced by Shopee Mall in Batam City, where a decline in transaction volume suggests potential erosion in consumer confidence. The research aims to examine the influence of brand image, product quality, and consumer trust on purchasing decisions within this e-commerce environment. A quantitative method was employed, involving 100 respondents selected using the Lemeshow sampling formula. Data were collected through structured questionnaires, which were tested for validity and reliability prior to analysis. The analytical tools included classical assumption tests, multiple linear regression, and hypothesis testing using both t-tests (partial effect) and F-tests (simultaneous effect). The results indicate that brand image (t = 2.723, p = 0.008), product quality (t = 2.569, p = 0.012), and trust (t = 3.377, p < 0.001) each have a positive and significant effect on purchase decisions. Collectively, the three variables explain 68.6% of the variation in purchase behavior (R² = 0.686; F = 69.965, p < 0.001). The findings underscore the importance of fostering strong brand equity, maintaining consistent product quality, and enhancing consumer trust to strengthen online purchasing behavior in competitive e-commerce platforms such as Shopee Mall.